Filsafat Pendidikan Anti Korupsi: Internalisasi Nilai Islam dan Budaya Bangsa: Philosophy of Anti-Corruption Education: Internalization of Islamic and National Culture Values - Kulsum, Siti Umi; Indriyani, Desy; Huda, Miftakhul (FAI UIM, 2023)
Schools as centers of education must be able to implement anti-corruption education, especially in cultivating anti-corruption behavior in every individual in the academic environment. Educators must be able to arouse students' curiosity about the urgency of this material so that they are able to stay away from corrupt behavior. The purpose of this study was to determine the philosophy of anti-corruption education as an effort to internalize Islamic religious values and national culture in educational institutions. The method used in this study was a literature study. The results of this study indicate that, ontologically, corruption means misappropriation of institutional funds for personal gain. Corruption in an epistemological review examines the personal factors of humans and the factors that cause someone to commit corruption. Based on the axiological review of anti-corruption, Islamic education has values that are in line with the spirit of anti-corruption as a cultural value of the nation, such as honesty, patience, and contentment. This study has implications for the importance of educators in instilling in students how big the negative impact of corruption is for themselves, their families, and the people around us.